Influence of patterns of neonatal transfers on breastfeeding outcomes. (27th May 2021) - Sinclair, Lynn; Spence, Kaye; Galea, Claire; ,
Abstract : Aim: To investigate/evaluate the impact of hospital transfers on breastfeeding outcomes for infants requiring neonatal intensive care and to explore approaches to supporting lactation and breastfeeding. Methods: A national study of two cohorts of infants admitted to the nine neonatal intensive care units (NICUs) in New South Wales (NSW) Australia using data sourced from a prospectively collected NICUS data collection. Results: A total of 7829 infants were admitted to the nine NICUs in NSW for two 18‐month cohorts (2012/2013 and 2015/2016) and were included in the study. These infants experienced 17 238 transfers to 107 different hospitals during the study period. Multiple transfers and low gestational age were independently associated with lower breastfeeding rates at hospital discharge across both cohorts. Extremely preterm infants and those with the greatest number of hospital transfers are least likely to be breastfed at time of discharge. Breastfeeding rates remained unchanged over time. The level of lactation support varied across NICUs. Conclusion: This study highlights the challenges of establishing and maintaining breastfeeding for infants requiring intensive care who have had multiple hospital transfers for continuing or specialist care. There is wide variation in lactation support across facilities. The importance of a consistent approach, education programmes and the provision of appropriate lactation support is emphasised.